A highly selective tri‐band bandpass‐to‐bandstop filter with the third band independently tunable. Issue 3 (17th October 2021) - Yang, Hong; Zhang, Dewei; Zhang, Junjie; Wang, Xian; Lv, Dalong; Zhang, Yi; Zhou, Dongfang
Abstract: A highly selective tri‐band bandpass (BP)‐to‐bandstop (BS) filter with the third tunable band and the other two fixed ones is proposed in this article. This filter is based on a novel crossed resonator that is composed of a two‐end‐open UIR with an open stub and a short stub connected in parallel on both sides of the resonator center. A PIN diode is utilized to achieve BP‐to‐BS switchable characteristics. Then, varactor diodes loaded at the open stub are employed to obtain the independently tunable third band. In addition, due to the symmetry of the resonator structure, the even‐ and odd‐ mode analysis method is used to derive the resonant frequencies. For validation, a tri‐band BP‐to‐BS filter operating at 2.4 GHz (WLAN), 3.3 GHz (WiMAX), and 4.9 GHz (LAA/LTE‐U) is designed, manufactured, and measured that achieves the continuous frequency tuning range (FTR) of the third band from 4.52 to 4.90 GHz with return loss (RL) better than 10.05 dB under the BP characteristic, from 4.55 to 4.90 GHz with the rejection level (RL) higher than 15.53 dB under the BS characteristic. The measured results agree well with the simulated ones. Abstract : In this article, a tri‐band BP‐to‐BS filter with the third band tunable and the other ones fixed using the crossed resonator is proposed, analyzed and demonstrated. Combined with the proposed coupling structure, the M and Qe can be met to form the tri‐band. The PIN diode is applied as a switch to alter BP‐to‐BS characteristic. Loading varactor diode at the end of the open stub can independently tune the frequency of the third passband and stopband. The results indicate high selectivity and compact size are achieved, and the proposed filter has significant potential in adjustable and multi‐purpose RF systems.